2022
DOI: 10.1002/admt.202101549
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Multifunctional Composite for Passive Sensing, Power Harvesting, and In Situ Damage Identification with Enhanced Mechanical Performance

Abstract: A multifunctional fiber‐reinforced composite with passive self‐sensing, energy‐harvesting, and damage detection capabilities is presented. Here, barium titanate piezoelectric microparticles are deposited on basalt fibers by a scalable, low‐cost, environmentally friendly continuous feed‐through process. The resulting composite derives a superior interlaminar shear strength from the microparticle‐modified fiber–matrix interfaces. The composite also demonstrates passive self‐sensing capabilities that produce elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…This method was further upgraded to integrate TiO2 nanoparticles on the carbon fiber surfaces, where the resulting composites exhibited an 18% increment in ILSS while exhibiting an improved strain-sensing response [18]. More recently, we have demonstrated that even piezoelectric BaTiO3 microparticles of diameter ~200 nm could also be integrated on the fiber surfaces resulting in a passive sensing composite with ~ 20%enhanced ILSS [1,4,19]. While being chemically less intensive, this method can be easily scaled up for large-scale industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…This method was further upgraded to integrate TiO2 nanoparticles on the carbon fiber surfaces, where the resulting composites exhibited an 18% increment in ILSS while exhibiting an improved strain-sensing response [18]. More recently, we have demonstrated that even piezoelectric BaTiO3 microparticles of diameter ~200 nm could also be integrated on the fiber surfaces resulting in a passive sensing composite with ~ 20%enhanced ILSS [1,4,19]. While being chemically less intensive, this method can be easily scaled up for large-scale industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work also demonstrated that ceramic nanoparticles (TiO 2 , BaTiO 3 , and SiC) could be efficiently integrated at the fiber-matrix interphases, bettering the FRPCs' interlaminar shear strength. [21][22][23][24][25] Although fiber sizing is a straightforward way to boost the fiber-matrix interaction, selecting compatible yet universal sizing elements is crucial. [26,27] Alternatively, the structural hierarchy could be created by directly dispersing the nanofillers into the polymer matrix and used in composite casting for IFSS improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work also demonstrated that ceramic nanoparticles (TiO 2 , BaTiO 3 , and SiC) could be efficiently integrated at the fiber‐matrix interphases, bettering the FRPCs’ interlaminar shear strength. [ 21–25 ] Although fiber sizing is a straightforward way to boost the fiber‐matrix interaction, selecting compatible yet universal sizing elements is crucial. [ 26,27 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the high internal stress after curing, which leads to the limitation of applying epoxy resinbased composites, people often use fibers to toughen the epoxy resin composites. [1][2][3][4][5][6][7] Fiber-reinforced composites can enhance the composite material's strength, stiffness, and corrosion resistance. Compared with traditional glass and carbon fibers, basalt fibers have the characteristics of lightweight, higher modulus, lower energy consumption, higher strength, higher corrosion resistance, higher fatigue resistance, and better compatibility.…”
Section: Introductionmentioning
confidence: 99%